VOLATILITY ANALYSIS USING THE EGARCH METHOD: CASE STUDY OF BBCA, BMRI, BRIS - Suhendro, Suhendro; Siddi, Purnama (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACTThis study aimed to test the volatility model of BBCA and BMRI stocks on the IDX. The research problem is whether there is an influence of BBCA and LQ45 volatility on BMRI and vice versa. The study also tested whether BRIS's volatility was influenced by its majority shareholder, BMRI. The EGARCH model analyzed daily return data for 2015-2022 in bearish/bullish markets. The results showed that the data experienced heteroscedasticity problems, and the EGARCH Student's model was selected. The volatility of BBCA and BMRI returns does not affect each other but is influenced by LQ45 when bearish/bullish. The volatility of BRIS returns is influenced by BMRI only when it is bearish and the LQ45 index when bullish. The implications of the research prove the independence of stock investors (BMRI and BBCA) in making decisions. However, it was indicated that both investors were influenced by the decisions of most investors, which was reflected in the significance of the LQ45 index.ABSTRAKTujuan penelitian ini adalah untuk menguji model volatilitas saham BBCA dan BMRI di BEI. Permasalahan penelitiannya adalah apakah terdapat pengaruh volatilitas return saham BBCA dan LQ45 terhadap BMRI dan sebaliknya. Penelitian tersebut juga menguji apakah volatilitas BRIS dipengaruhi oleh return saham pemegang saham mayoritasnya, BMRI. Model EGARCH digunakan untuk menganalisis data return harian tahun 2015-2022 saat pasar bearish/bullish. Hasil penelitian menunjukkan bahwa data mengalami masalah heteroskedastisitas dan model EGARCH Student's-t yang dipilih. Volatilitas return BBCA dan BMRI tidak saling mempengaruhi, namun dipengaruhi oleh LQ45 saat bearish/bullish. Volatilitas imbal hasil BRIS hanya dipengaruhi oleh BMRI saat bearish dan indeks LQ45 saat bullish. Implikasi penelitian membuktikan independensi investor saham (BMRI dan BBCA) dalam mengambil keputusan. Namun kedua investor tersebut terindikasi dipengaruhi keputusan mayoritas investor yang tercermin signifikansinya indeks LQ45.